Sistem Rekomendasi Penerima Bantuan Program Indonesia Pintar Menggunakan Multi Criteria Decision Making - Perbawa, Doddy Satrya (Jurnal Ilmiah FIFO, 2023)
The government continues to strive to increase equality, equity and access to education through various programs, including the Smart Indonesia Program (PIP). Process PIP recipient students selection is quite  complex process if carried out without adequate information technology support. This condition was also experienced by SMKN 6 Surakarta. The large number of students registering for PIP, and data processing that is still being done from piles of files are conditions that influence the slow PIP student selection committee performance. The committee must select, search and verify a lot of student data. Selection process requires a long time and a high level of accuracy so it is prone to errors caused by human error. In this research, a Decision Support System was created using the Analytical Hierarchy Process (AHP) method and the Multi-Objective Optimization by Ratio Analysis (MOORA) method. AHP method in this research aims to determine each criterion weight before the alternative ranking stage. The aim of using the MOORA method is to determine the ranking of alternatives after determining the weighting using AHP. The criteria used in this research are: Ownership of cards/letters, parents' income and number of siblings. Each criterion has sub-criteria and values that will be used in the AHP method calculations. From the results of the accuracy test by comparing data from 2020 to 2022, the accuracy results for 2020 were 94.4%, 95.5% for 2021 and 93.6% for 2022.